Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.jaim.2021.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights for an anti-osteoporotic properties of Litsea glutinosa on Saos-2 cells: An in-vitro approach

Abstract: Osteoporosis is a skeletal disease that is identified by the deterioration of micro-architecture of bone tissue, leading to enhanced bone brittleness and a consequential increase in fracture threat. There are many treatments available for osteoporosis such as bisphosphonate therapy, hormonal replacement therapy, herbal therapy etc. For decades, there are several herbs that are attributed to have anti-osteoporotic effects however the candidate genes involved in it remained unknown. In line with this, the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A conceivable explanation for the observed cytotoxicity, according to in silico docking, is the stabilization of a topoisomerase II (β) DNA-enzyme complex [ 28 ]. In in vitro studies on Saos-2 cells, methanolic extract of L. glutinosa bark significantly downregulates the apoptotic and proliferative markers in Saos-2 osteocytes [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A conceivable explanation for the observed cytotoxicity, according to in silico docking, is the stabilization of a topoisomerase II (β) DNA-enzyme complex [ 28 ]. In in vitro studies on Saos-2 cells, methanolic extract of L. glutinosa bark significantly downregulates the apoptotic and proliferative markers in Saos-2 osteocytes [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that EGR2 is a zinc finger transcription factor, and EGFR signaling activates the MAPK/ERK pathway to stimulate EGR2 expression ( 57 ). Further, mounting evidence indicates that IL-27 inhibits RANKL-mediated osteoclast differentiation ( 8 ) in an EGR2-dependent manner ( 10 ). A previous report suggests that BMP-2-induced Smad1 protein activation leads to JUNB synthesis, which is involved in the trans-differentiation of myoblasts to osteoblasts and contributes to bone repair after OP ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients with osteoporotic fractures often require hospitalization, resulting in poor quality of life, long-term medical care, disability, and even death ( 7 ). This creates a substantial economic and social burden worldwide and is a global public health challenge ( 8 , 9 ). Due to its asymptomatic nature, patients with OP are often not diagnosed until the first osteoporotic fracture occurs.…”
Section: Introductionmentioning
confidence: 99%